Open Skies over the Middle East - Cristea, Anca; Hillberry, Russell; Mattoo, Aaditya (World Bank, Washington, DC, 2015)
The dynamism of air traffic markets in the Middle East obscures the persistence of restrictions on international competition. But how important are such restrictions for passenger traffic? This longer paper by the same title that this Quick Note is based on uses detailed data on worldwide passenger aviation to estimate the effect of air transport policy on international air traffic2. The policy variable is a quantitative measure of the commitments under international agreements. The paper analyzes, and for the first time, not only bilateral agreements, but also plurilateral agreements such as the one between Arab states. The analysis finds that more liberal policy is associated with greater passenger traffic between countries. Higher traffic levels appear to be driven primarily by larger numbers of city pairs being served, rather than by more passengers traveling along given routes. To demonstrate the quantitative implication of the estimates, two liberalization scenarios in the Middle East are evaluated.